Peptic Ulcer Disease (PUD): An overview of the History, Risk factors, Symptoms, Diagnosis Considerations and Conventional Management - Khan, Mohd. Shahid; Singh, Vijay; Arora, Pankaj (Asian Journal of Pharmaceutical Research and Development, 2021)
Gastric and duodenal ulcer (PUD), are upper gastrointestinal disorders sharing a common abnormality, too much acid and pepsin activity followed by inflammation, necrosis and ulceration of exposed mucosa. H. Pylori infection, use of NSAIDs and stress are the major risk factors that lead to the occurrence of PUD. With the introduction of proton pump inhibitors (PPIs) and antibiotics against H. Pylori resolution of symptom and rapid ulcer healing was obtained but cure of PUD has failed. However, new challenges have emerged due to increasing antibiotic resistance of H. pylori. Management of peptic ulcer needs accurate identification of the ulcerogenic cause in the individual patient for proper selection of therapy.